A Rare Presentation of Acquired Port Wine Stain in an Elderly Male - Jha, Prasanna Kumar; Singh, Satyendra Kumar (Nepalese Medical Journal, 2021)
Acquired port wine stain though an uncommon entity that develops later in life, resembles congenital port wine stain morphologically and histologically. Congenital port wine stains are vascular lesions caused by progressive ectasia of blood vessels which is located in the vascular plexus of the dermis. Congenital port-wine stains may be associated with Sturge Weber syndrome causing neurological and eye abnormalities such as glaucoma. Here we report a 60-year-old male presenting with a complaint of asymptomatic reddish patches over the nose for 15 years.